STRATEGI PENGEMBANGAN PONDOK PESANTREN ERA MODERN - Wahyu Choerul Cahyadi; Wibowo, Arif (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
Islamic boarding schools (pondok pesantren) are Islamic educational institutions that play a strategic role in character formation and the development of Islamic scholarship in Indonesia. Social change, technological advancement, and increasing demands for professionalism in educational management have encouraged pesantren to adopt more systematic management approaches. This article aims to examine strategic management in the development of Islamic boarding schools in the contemporary era by analyzing theoretical concepts, implementation practices, and their compatibility with the characteristics of pesantren as value- and tradition-based Islamic educational institutions. This study employs a qualitative approach using a library research method. The findings indicate that strategic management is relevant to the development of pesantren, particularly in formulating vision and mission statements, conducting environmental analysis, and strengthening human resources as well as institutional independence. However, its implementation still faces challenges, especially in terms of strategy evaluation and control, as well as economic and financial capacity. The novelty of this article lies in the synthesis of modern strategic management with the Islamic value-based characteristics of pesantren. Abstrak Pondok pesantren merupakan lembaga pendidikan Islam yang memiliki peran strategis dalam pembentukan karakter dan pengembangan keilmuan keislaman di Indonesia. Perubahan sosial, perkembangan teknologi, dan meningkatnya tuntutan profesionalisme pengelolaan pendidikan mendorong pesantren untuk mengadopsi pendekatan manajemen yang lebih sistematis. Artikel ini bertujuan untuk mengkaji manajemen stratejik dalam pengembangan pondok pesantren pada era modern saat ini dengan menelaah konsep teoretis, implementasi, serta kesesuaiannya dengan karakteristik pesantren sebagai lembaga pendidikan berbasis nilai dan tradisi Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan. Hasil kajian menunjukkan bahwa, manajemen stratejik relevan diterapkan dalam pengembangan pesantren, terutama dalam perumusan visi dan misi, analisis lingkungan, serta penguatan sumber daya manusia dan kemandirian lembaga. Namun, implementasinya masih menghadapi kendala, khususnya pada aspek evaluasi dan pengendalian strategi dan kekuatan ekonomi atau keuangan. Kebaruan artikel ini terletak pada sintesis manajemen stratejik modern dengan karakteristik pesantren berbasis nilai keislaman.